Analyzing performance of BUMDES: Learn from waste bank and clean water units. Issue 1 (October 2020) - Asis, A; Salam, M; Siregar, A R; Rahmadanih,; Salman, D; Jamil, M H; Supratman,
Abstract: The research aimed to analyze the management performance of the BUMDES (Village-Owned Business Enterprise). The research used Case Study Method to provide detailed perspectives of individual village leaders who directly engage at very beginning of the establishment of the BUMDES in each village. Then, we took the advantage of in-depth interview for data collection. Twenty third village leaders selected purposively were interviewed. Data analysis approach used in this research is descriptive qualitative method for making some descriptions of the BUMDES. It is very clear that the process of establishing the BUMDES have fulfilled the requirements of the Indonesian government regulation. The results show that, types of businesses BUMDES members are savings and loan unit, service business unit, clean water management unit, cattle fattening unit, waste banks unit, photocopy unit, and marketing of agricultural products unit, etc. The BUMDES in the district has made a real contribution to the rural economy. It's contribution to the Local Government Revenue is a prove of a relatively good management performance indicator of the BUMDES. It is also implicit that the BUMDES has become one of the factors driving the village economy that has encouraged the absorption of rural-labor in rural areas.